2014
DOI: 10.1186/1478-4491-12-43
|View full text |Cite
|
Sign up to set email alerts
|

The effects of health worker motivation and job satisfaction on turnover intention in Ghana: a cross-sectional study

Abstract: BackgroundMotivation and job satisfaction have been identified as key factors for health worker retention and turnover in low- and middle-income countries. District health managers in decentralized health systems usually have a broadened ‘decision space’ that enables them to positively influence health worker motivation and job satisfaction, which in turn impacts on retention and performance at district-level. The study explored the effects of motivation and job satisfaction on turnover intention and how motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
208
2
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(253 citation statements)
references
References 48 publications
32
208
2
11
Order By: Relevance
“…Several studies have confirmed the negative relation of job satisfaction and turnover intention. [34][35][36]. Employees with low job satisfaction decide to quit the organization in the hope of finding a more satisfactory job.…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 99%
“…Several studies have confirmed the negative relation of job satisfaction and turnover intention. [34][35][36]. Employees with low job satisfaction decide to quit the organization in the hope of finding a more satisfactory job.…”
Section: Job Satisfaction and Turnover Intentionmentioning
confidence: 99%
“…Employees are the most significant resources of healthcare organizations depend on its workforce job satisfaction. A study conducted by Bonenberger [1] findings suggest that the "Effective human resource management practices at district level influence health worker motivation and job satisfaction, thereby reducing the likelihood for turnover". Effective management is crucial to improve the nature of working relationship of employee with their employing organization.…”
Section: Describementioning
confidence: 99%
“…In Vietnam, limited research has examined healthcare workers' job satisfaction, the findings suggest that job satisfaction is low because of insufficient salaries and benefits, poor facilities and equipment, and a lack of professional development opportunities (Tran, Van, & Hinh, 2013;Nguen, Duong, & Vu, 2016). These findings concur with the results of studies conducted in other developing countries such as Uganda (Luboga, Hagopian, Ndiku, Bancroft, & McQuide, 2011), Senegal (Rouleau, Fournier, Philibert, Mbengue, & Dumont, 2012), Tanzania (Mbaruku, Larson, Kimweri, & Kruk., 2014), Afghanistan, Malawi (Fogarty et al, 2014), and Ghana (Bonenberger, Aikins, Akweongo, & Wyss, 2014).…”
Section: Introductionmentioning
confidence: 99%